Patients tremble analysis under different camera placement in critical care - Muhammad Naufal, Mansor; Sazali, Yaacob, Prof. Dr.; R. Nagarajan, Prof. Dr.; Muthusamy, Hariharan, Dr. (Science Academy, 2011)
Link to publisher's homepage at http://www.sciacademypublisher.com/